EVALUATION AND MECHANICAL PROPERTIES OF KEVLAR S GLASS AND CARBON FIBER WITH GRAPHITE POWDER USING HANDLAYUP TECHNIQUE (International Journal of Food and Nutritional Sciences, 2022)
Composite materials are made of two or more constituent materials that are combined to create a materialwith superior properties to those of the individual materials. Synthetic fibers, such as glass fiber, carbon fiber, and aramidfiber, are often used as the reinforcing material in composite materials. These fibers are strong, lightweight, and have goodfatigue resistance